2014
DOI: 10.3390/rs6042864
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Coarse-Resolution Land Cover Products Using CASI Hyperspectral Data in an Arid Zone in Northwestern China

Abstract: Abstract:The accuracy of different coarse-resolution land cover products is an important consideration for product users at the regional or global scale, and different evaluation methods inevitably result in discrepancies in accuracy for the same land cover product. The remote sensing community has responded to this increased interest by improving methodologies for more accurately evaluating the correctness of land cover information. In this study, a pixel-based hierarchical classification strategy followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Rule (ii) helped to reduce 500 m pixel edge effects in situations where there were possible changes in the underlying land cover. Rule (iii) was introduced because the homogeneous pixels had a higher classification accuracy [34]. Rule (iv) helped to reduce the GEE cloud-based platform provides massive amounts of multi-source satellite data and high-performance computation service, making the computation between different satellite imagery a relatively fast and flexible process.…”
Section: Automatic Collection Of Samples From Modis Land Cover Productsmentioning
confidence: 99%
“…Rule (ii) helped to reduce 500 m pixel edge effects in situations where there were possible changes in the underlying land cover. Rule (iii) was introduced because the homogeneous pixels had a higher classification accuracy [34]. Rule (iv) helped to reduce the GEE cloud-based platform provides massive amounts of multi-source satellite data and high-performance computation service, making the computation between different satellite imagery a relatively fast and flexible process.…”
Section: Automatic Collection Of Samples From Modis Land Cover Productsmentioning
confidence: 99%
“…A CASI-1500 hyperspectral sensor consisting of an Instrument Control Unit (ICU), Sensor Head Unit (SHU), and monitor was employed for the hyperspectral surveying over study area for the seabed classification. The CASI-1500 system was integrated with a POSAV 410 Inertial Measurement Unit (IMU) that records aircraft motion (roll, pitch, and heading) using gyroscopes and accelerometers and that also records aircraft position using differential GPS [9].…”
Section: Sensor Backgrounds and Hyperspectral Surveyingmentioning
confidence: 99%
“…The data from this flight was used to determine the linear and angular offsets between the CASI-1500 and the co-mounted sensors (POSAV 410 and GPS) using ITRES bundle adjustment software [8,10]. This allowed for measurements made by the IMU and GPS to be referenced to the co-mounted CASI SHU during post-processing, thereby increasing geometric accuracy in the final georeferenced imagery [9]. The installation and internal sensor offsets determined from this calibration site were applied in the geocorrection process to all imagery collected during the installation of the CASI system.…”
Section: Pre-processing Of Hyperspectral Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary validation of the corrected CASI reflectance showed that the absolute differences were 1.5% (relative difference 5.93%) in the visible range of the spectrum (400 nm-700 nm) and 2.5% (relative difference 7.89%) in the near infrared (700 nm-1055 nm), compared with the reflectance of a homogenous concrete surface measured synchronically in the ground campaign. Land cover types were mapped using the CASI BRF; this classification technique, detailed in the work of Wang et al [27], is based on the ratio vegetation index (RVI). The FEA contains four land cover types: cropland (mainly corn), manmade features, bare soil, and bushes, as shown in Figure 1.…”
Section: A Compact Airborne Spectrographic Imager (Casi)-based Airbormentioning
confidence: 99%